Actualized lower body contouring surgery after bariatric surgery - a nationwide register-based study - Pajula Susanna; Gissler Mika; Jyränki Janne; Tukiainen Erkki; Koljonen Virve (TAYLOR & FRANCIS LTD, 2022)
Massive weight loss might lead to excess skin folds causing functional, physical, and psychosocial discomfort. Following bariatric procedures, an increasing number of patients are seeking lower body contouring surgery (LBCS). The proportion of bariatric patients who undergo LBCS is largely unknown. The aim of this current study was to analyse the incidence and realization of LBCS in bariatric patients in Finland. National retrospective register linkage study including all adult patients who received bariatric surgery in Finland during 1998-2016. The data were obtained from the Finnish national health registers maintained by the Finnish Institute for Health and Welfare. Altogether 1089 (14.1%) of 7703 bariatric patients underwent LBCS during the study period. The majority of the LBCS procedures were abdominoplasty (89%). Median latency between bariatric surgery and LBCS was 31 months. The patients with LBCS were younger (p < 0.001) and received sleeve gastrectomy (p < 0.001). We revealed an annual correlation between LBCS and bariatric procedures (r = 0.683). With a two-year latency between the bariatric and post-bariatric operations, the correlation co-efficiency was strong (r = 0.927). LBCS operations ranged from 5 to 215 per hospital district. Most LBCSs (97.3%) were performed in public hospitals, and some (41%) were performed in university hospitals. This study shows that only 14.1% of bariatric patients undergo LBCS. There is a correlation between bariatric procedures and succeeding plastic surgical reconstructive procedures.